Low-dose melittin is safe for intravitreal administration and ameliorates inflammation in an experimental model of uveitis - Brenda Fernanda Moreira Castro; Carolina Nunes da Silva; Lídia Pereira Barbosa Cordeiro; Sarah Pereira de Freitas Cenachi; Daniel Vitor Vasconcelos-Santos; Renes Resende Machado; Luiz Guilherme Dias Heneine; Luciana Maria Silva; Armando Silva-Cunha; Silvia Ligório Fialho (Elsevier, 2022)
Uveitis is a group of sight-threatening ocular inflammatory disorders, whose mainstay of therapy is associated with severe adverse events, prompting the investigation of alternative treatments. The peptide melittin (MEL) is the major component of Apis mellifera bee venom and presents anti-inflammatory and antiangiogenic activities, with possible application in ophthalmology. This work aims to investigate the potential of intravitreal MEL in the treatment of ocular diseases involving inflammatory processes, especially uveitis. Safety of MEL was assessed in retinal cells, chick embryo chorioallantoic membranes, and rats. MEL at concentrations safe for intravitreal administration showed an antiangiogenic activity in the chorioallantoic membrane model comparable to bevacizumab, used as positive control. A protective anti-inflammatory effect in retinal cells stimulated with lipopolysaccharide (LPS) was also observed, without toxic effects. Finally, rats with bacille Calmette-Guerin- (BCG) induced uveitis treated with intravitreal MEL showed attenuated disease progression and improvement of clinical, morphological, and functional parameters, in addition to decreased levels of proinflammatory mediators in the posterior segment of the eye. These effects were comparable to the response observed with corticosteroid treatment. Therefore, MEL presents adequate safety profile for intraocular administration and has therapeutic potential as an anti-inflammatory and antiangiogenic agent for ocular diseases.